Biomechanical Energy: Biomechanical Energy‐Driven Hybridized Generator as a Universal Portable Power Source for Smart/Wearable Electronics (Adv. Energy Mater. 12/2020). Issue 12 (26th March 2020) - Rahman, Muhammad Toyabur; Rana, SM Sohel; Salauddin, Md; Maharjan, Pukar; Bhatta, Trilochan; Park, Jae Yeong
Abstract : In article number 1903663, Jae Yeong Park and co‐workers demonstrate an elastic‐impact‐based nonresonant hybridized generator (EINR‐HG) for biomechanical energy harvesting at low frequency vibrations. Introducing a soft‐magnetic material‐based flux‐concentrator and nanowire/nanofiber‐based triboelectric materials significantly improves the output performance of the EINR‐HG. The EINR‐HG serves as a universal portable power source for state‐of‐art smart/wearable electronics under diverse human‐induced vibrations at different carrying positions, such as in a backpack.